Teladan Spiritualitas Figur Nuh: Standar Kehidupan Rohani Bagi Pemimpin Kristen Masa Kini - Marnaek Nainggolan; Happy Fasigita Paradesha (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2022)
This research is a study of the spiritual example of the figure of Noah as a standard of spiritual life for today's Christian leaders. The Bible provides a wealth of information about the spirituality of Christian leaders. The information presented includes the characteristics of Christian leaders which include personal character, humility, wisdom, servant leaders and exemplary leaders. Various explanations about the background and living conditions of the leaders of God's people are presented in both the Old Testament and the New Testament. The author observes that the presence of leaders in the Bible is a guide to bring God's people to a deeper spiritual life. In this study, the author examines Noah's leadership. A leadership model that is not easily carried out by leaders in the midst of the moral condition of the environment that is so worrying, however, Noah still has the right attitude of life before God and his community. This study aims to provide a historical analysis of (1) Spirituality in Noah's leadership. (2) Application of Noah's leadership experience for Christian Leaders today. The method used is descriptive analysis in the book of Genesis 6:9. From the results of this study, it is explained about the life of Noah who has a spiritual example. First, the example of Noah's spirituality as a righteous person in the eyes of God. Second, Noah's Exemplary Spirituality as a person who was blameless among people. Third, the example of Noah's Spirituality as a person who lived in association with God. This example is very important as a reference for today's Christian leaders both as individuals in their leadership positions and also for all God's people who want to improve their spirituality and character.AbstrakPenelitian ini merupakan kajian terhadap teladan spiritual figur Nuh sebagai standar kehidupan rohani bagi pemimpin Kristen masa kini. Alkitab memberi banyak informasi mengenai spiritualitas pemimpin Kristen. Informasi yang disajikan mencakup tentang sifat-sifat pemimpin Kristen yang meliputi pribadi yang berkarakter, rendah hati, berhikmat, pemimpin yang melayani dan keteladanan pemimpin. Berbagai penjelasan tentang latar belakang dan kondisi kehidupan para pemimpin umat Tuhan disajikan baik dalam kitab Perjanjian Lama maupun Perjanjian Baru. Penulis mengamati bahwa kehadiran para pemimpin dalam Alkitab adalah sebagai penuntun untuk membawa umat Tuhan pada kehidupan spiritual yang lebih dalam lagi. Dalam penelitian ini penulis mengkaji kepemimpinan Nuh. Suatu model kepemimpinan yang tidak mudah dilakukan oleh para pemimpin ditengah kondisi moralitas lingkungannya yang begitu meprihatinkan namun, Nuh tetap memiliki sikap hidup yang benar dihadapan Allah dan komunitasnya. Penelitian ini bertujuan untuk memberikan analisis historis mengenai (1) Spiritualitas dalam kepemimpinan Nuh. (2) Penerapan dari pengalaman kepemimpinan Nuh bagi Pemimpin Kristen masa kini. Metode yang digunakan adalah analisis deskriptif pada kitab Kejadian 6:9. Dari hasil penelitian ini dijelaskan tentang kehidupan Nuh yang memiliki teladan spritual. Pertama, Teladan spiritualitas Nuh sebagai pribadi yang benar di mata Tuhan. Kedua, Teladan Spiritualitas Nuh sebagai seorang yang tidak bercela di antara orang-orang. Ketiga, Teladan Spiritualitas Nuh sebagai orang yang hidup bergaul dengan Allah. Teladan ini sangat penting sebagai acuan bagi pemimpin Kristen masa kini baik sebagai individu dalam posisi kepemimpinannya dan juga bagi semua umat Tuhan yang ingin meningkatkan spiritualitas dan karakter mereka.